Пленэрная живопись как художественный опыт погружения в образ изображаемого объекта - Молчанова-Дудченко, Е.А. (Культура народов Причерноморья, 2013)
Пленэрная живопись является одним из самих распространенных среди художников
жанров изобразительного искусства. Все художники проходят через обучение живописи на пленэре, где
каждый мастер выбирает выразительный и интересный натурный материал, который удовлетворяет
его творческие амбиции. Особую роль в этом процессе играет момент «погружения» в объект, чувство
восторга соединения с ним и принятие его. Автор статьи анализирует нюансы пленэрной работы и
приводит практические советы великих живописцев прошлого.
Ключевые слова: живопись, метод, пленэр, объект, этюд, натурный материал, художественный образ. Пленерний живопис є одним з самих поширених серед художників жанрів образотворчого
мистецтва. Всі художники проходять через навчання живопису на пленері, де кожен майстер вибирає
виразний і цікавий натурний матеріал, який задовольняє його творчі амбіції. Особливу роль у цьому
процесі відіграє момент «занурення» в об'єкт, почуття захоплення з'єднання з ним і прийняття його.
Автор статті аналізує нюанси пленерної роботи і наводить практичні поради великих живописців
минулого.
Ключові слова: живопис, метод, пленер, об’єкт, етюд, натурний матеріал, художній образ. Plein-air painting is one of the popular and favorite genres of art among the painter. All painters of
past and present went through training painting on the plein-air, where each master chooses by the composition,
color, assortment of items the expressive and interesting natural material that is satisfies his creative ambitions.
A special role in this process is the time of "immersion" into the object, a sense of delight to connect to it and
taking it. In the article is provided practical advices of the great painters of the past (Konstantin Korovin,
Appolinary Vasnetsov, Shi Tao), whose plein-air works is radiated the living light and carried a sense of
trepidation and motility nature.
The author concludes that plain-air is helped to establish between the artist and the object of the interrelation
that is formed under the influence of both objective and subjective factors.
The product is born only with the active inclusion figurative a personal and psychological quality of the author,
his creative talent is allows to fully incorporating this mechanism and combines two worlds - external and
internal. Plein-air painting is a pure source, which is nurtures of life-giving energy of artists, and those who has
experienced the "rapture of finding yourself through the surrounding world" to transforms themselves and
transforms this world.
Keywords: painting, method, plein-air, object, etude, nature material, artistic image.